Brand Management - Fíla, Petr (2018)
The bachelor thesis on Brand Management topic is focused on solving given problems in specific conditions of economic practice and on the basis of the theoretical and methodological knowledge, obtained by studying professional literature from the area and their subsequent application into the Czech company EYELEVEL, s.r.o.